Database Systems for Advanced Applications 17th International Conference, DASFAA 2012, International Workshops: FlashDB, ITEMS, SNSM, SIM3, DQDI, Busan, South Korea, April 15-18, 2012, Proceedings - Yu, Hwanjo; Yu, Ge; Hsu, Wynne; Moon, Yang-Sae; Unland, Rainer; Yoo, Jaesoo (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the workshop proceedings of the 17th International Conference on Database Systems for Advanced Applications, DASFAA 2012, held in Busan, South Korea, in April 2012. The volume contains five workshops, each focusing on specific area that contributes to the main themes of the DASFAA conference: The Second International Workshop on Flash-based Database Systems (FlashDB 2012), the First International Workshop on Information Technologies for Maritime and Logistics (ITEMS 2012), the Third International Workshop on Social Networks and Social Media Mining on the Web (SNSMW 2012), the Second International Workshop on Spatial Information Modeling, Management and Mining (SIM3 2012), and the Fifth International Workshop on Data Quality in Integration Systems (DQIS 2012).